Pelatihan Kewirausahaan Digital Facebook Sayuran Kangkung Di Bengkulu Tengah - Rusminita, Esi; Hanila, Siti (LPPM Universitas Dehasen Bengkulu, 2024)
in increasing interest in entrepreneurship for the community. starting a business through technological advances and being ready to face business opportunities in the digital era This Community Service Activity is entitled